(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Global financial systems have undergone significant change as a result of the COVID-19 epidemic, which has sped up the transition to digital financial services (DFS). DFS became a vital remedy as lockdowns and social distancing measures caused extensive interruptions to traditional banking institutions, allowing people and companies to carry on with their economic activity. This essay identifies the main advantages, disadvantages, possibilities, and hazards of DFS’s participation during the COVID-19 epidemic. According to the report, DFS was essential in improving financial inclusion, providing effective and scalable substitutes for conventional banking, and guaranteeing company continuity throughout the crisis. But it also brought to light important issues including operational inefficiencies, cybersecurity threats, and the digital divide. There were plenty of development prospects, especially in the fields of regulatory adaptation, decentralized finance (DeFi), and financial innovation. DFS made it possible to construct equitable regulatory frameworks, enhance financial access in disadvantaged areas, and create innovative business models. However, in order to reduce new dangers, the pandemic highlighted the necessity of strong cybersecurity systems, more transparent regulations, and infrastructure investment. These findings’ ramifications highlight the need for cooperation between regulators, financial institutions, fintech firms, and lawmakers in order to close the gaps shown by the epidemic. Stakeholders must concentrate on closing the digital gap, boosting user confidence with better security measures, and making sure that underserved groups benefit from DFS going ahead. DFS can significantly contribute to promoting sustainable financial inclusion, building global economic resilience, and influencing the direction of financial services by tackling these issues. In order to facilitate the long-term expansion and fair distribution of digital financial services, this paper advocates for smart investments and careful regulation.